Олон улсын авлигын төсөөллийн судалгааны агуулга, онцлог - Ж.ТӨРТОГТОХ (Politology, 2024)
Contents and Contexts of Global Corruption Perception Indexes In this paper, the author addresses common frames and specific peculiarities of the various corruption perception indexes in international arena. For instance, Corruption Perceptions Index of the Transparency International, Global Corruption Barometer and Bribe Payers Index are studied in the paper.